Advocating Worker Justice: A Catholic Ethicist's "Toolkit". Issue 2 (June 2017) - Beyer, Gerald J.
Abstract: Catholic moral theology possesses a number of tools that can be employed to promote worker justice. Some of these tools, such as Catholic social teaching on solidarity and workers' rights, have been used to this end before. However, advocates of workers' rights have seldom utilized other concepts, such as cooperation in evil, scandal, and evangelization. This essay provides a theoretical introduction to several tools in the "toolkit" of Catholic ethicists, engaging contemporary scholarship on them. It then applies the concepts to two cases in order to demonstrate their usefulness in the struggle for worker justice. Both cases involve Catholic universities, which means the ethical concepts introduced from the Catholic moral tradition should have normative status for these institutions. The first case entails a divestment campaign at the University of Notre Dame. The second case confronts the unjust treatment of adjunct faculty members at Catholic colleges and universities.